Toward a Regulated Future: Assessing Management of Zimbabwe's Informal Pharmaceutical Market (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study investigated the drivers of Zimbabwe's informal pharmaceutical market, focusing on its sources, distribution, and public health impact in Harare's Central Business District. This market raises significant concerns about medicinal drug quality and safety, contributing to antimicrobial resistance and undermining legitimate pharmaceutical businesses. The study employed a sequential explanatory mixed-methods design, collecting data from 51 participants, including consumers, vendors, regulators, and distributors, through questionnaires. The findings indicate that unregistered vendors source medicinal drugs primarily from locals and international suppliers. The distribution occurs directly to consumers through sachets at transport hubs, from car boots and street corners. Despite the perception among sellers and customers that these medicinal drugs are benign unless abused, the study highlights an urgent need for intervention. The study recommended policy actions, including public awareness campaigns on the dangers of unregulated medicinal drugs, strengthening border screening, and the implementation of a national health insurance policy to improve health delivery and outcomes in Zimbabwe. The study suggested an Informal Pharmaceutical Market Elimination Framework to protect consumers from unregulated medicinal products and promote the formal pharmaceutical market. The framework is legitimacy-sensitive and synchronous digital hierarchy–driven, escalates punishment for corrupt actors, and targets all involved stakeholders.